2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7417205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Modeling of Energy Consumption Behaviour for MIMO PLC Modems

Abstract: This paper presents a detailed measurement study of the electrical energy consumption of commercial Multiple Input Multiple Output (MIMO) Power Line Communications (PLC) modems. Based on these measurements, we propose a linear model that can be used to predict the energy consumed for different communication states and different operation modes of MIMO PLC modems (idle, standby, transmission, reception, variable data rates and variable Ethernet frame sizes). A multiple regression analysis is used to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…While the former is fixed and used to power the electronic circuitry of the transceiver, the latter is dependent on the traffic load. Experiments involving different PLC devices concluded that although static energy dominates the consumption, dynamic energy can sometimes be up to 50% [8]. It was further observed during the measurements that data reception typically consumes less energy than transmission by 20%-25%.…”
Section: Low-power Communication For Indoor Iot: Related Workmentioning
confidence: 90%
“…While the former is fixed and used to power the electronic circuitry of the transceiver, the latter is dependent on the traffic load. Experiments involving different PLC devices concluded that although static energy dominates the consumption, dynamic energy can sometimes be up to 50% [8]. It was further observed during the measurements that data reception typically consumes less energy than transmission by 20%-25%.…”
Section: Low-power Communication For Indoor Iot: Related Workmentioning
confidence: 90%